Cloning pigs as organ donors for humans. - Liangxue Lai
In order to overcome this shortage of organs, scientists have considered the possibility of using animals as a source of organs. Xenotransplantation, or xenografting, is the process of transplanting live organs between different species. ne choice of source animals will be of prime importance for xenotransplantation. Ideally, the donor animal would show immunological, anatomical, and physiological similarities to humans, possess organs of similar size to those of humans, would have a short generation interval, produce large litters, and show minimal risk of transmitting infectious agents to humans. Two groups of animals have been considered as potential donors: nonhuman primates and pigs. For several reasons, pigs, rather than nonhuman primates, are currently viewed as the most promising xenograft donors.
Keywords: Xenotransplantation; Anatomical; Hearts; Human-to-human transplantation; Immunological; Kidneys; Live organs; Livers; Lungs; Organ transplants; Organs; Pancreas; Physiological similarities; Pigs; Xenograft donors; Xenografting